2021
DOI: 10.7150/ijbs.44907
|View full text |Cite
|
Sign up to set email alerts
|

Homoharringtonine inhibited breast cancer cells growth via miR-18a-3p/AKT/mTOR signaling pathway

Abstract: Homoharringtonine (HHT), a natural alkaloid derived from the cephalotaxus, exhibited its anti-cancer effects in hematological malignancies clinically. However, its pesticide effects and mechanisms in treating solid tumors remain unclear. In this study, we found that HHT was capable of inhibiting tumor growth after 5-days treatment of breast cancer cells, MCF-7, in vivo. Furthemore, HHT also significantly inhibited the cancer cell growth and induced cell apoptosis in vitro. miRNA sequencing proved miR-18a-3p wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In H. pylori -associated gastric cancer, miR-18a-3p was increased and upregulating miR-18a-3p stimulated the growth and motility of gastric cancer cell lines in vitro ( Tsai et al, 2020 ). In addition, miR-18a-3p played a critical role in the inhibitory effect of homoharringtonine on breast cancer via targeting the AKT-mTOR pathway, and miR-18a-3p inhibitor facilitated HHT-induced cancer cell apoptosis ( Wang LB. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In H. pylori -associated gastric cancer, miR-18a-3p was increased and upregulating miR-18a-3p stimulated the growth and motility of gastric cancer cell lines in vitro ( Tsai et al, 2020 ). In addition, miR-18a-3p played a critical role in the inhibitory effect of homoharringtonine on breast cancer via targeting the AKT-mTOR pathway, and miR-18a-3p inhibitor facilitated HHT-induced cancer cell apoptosis ( Wang LB. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…mTOR-related signaling pathways regulates many important biological functions such as cell growth, metabolism, autophagy, homeostasis, protein synthesis, and immune response by forming two important complexes, mTORC1 and mTORC2 . The pathological relevance of mTOR signaling has been demonstrated in human cancers including breast, colon, and skin cancers. High mTOR expression or p-mTOR level was positively correlated with the degree of malignancy, depth of invasion, lymph node metastasis, and other adverse conditions of esophageal squamous cell carcinoma . In addition, the p-mTOR level also was associated with tumor metastasis and bad prognosis in patients with lung cancer after surgical resection .…”
Section: Mtor and Cancersmentioning
confidence: 99%
“…Our previous research found that HHT suppressed breast cancer cells growth and promoted apoptosis through miR-18a-3p-AKT-mTOR signaling pathway [11]. Besides, Shi et al [12] found that HHT could decrease LoVo cell growth by inhibiting EphB4 and its downstream signaling.…”
Section: Introductionmentioning
confidence: 99%